Automation, new technology and non-homothetic preferences - Clemens C. Struck; Adnan Velic (University College Dublin, UCD School of Economics, 2019)
To rationalize a substantial income share of labor despite progressive task automation over the centuries, we present a simple model in which demand moves along a vertically differentiated production structure toward goods of increasing sophistication. Automation of more sophisticated goods requires capital of increasing quality. Quality capital remains scarce along the growth path. This is why labor keeps up a substantial fraction of income. Real capital, however, that is capital measured in units of the quality of some base year, becomes abundant relative to labor. While our model features an entirely different mechanism, we show that its aggregate representation is the one of a neoclassical growth model with labor-augmenting technical change.
Keywords: E23; E24; E25; J23; J24; O14; O31; O33; 330; Uzawa's theorem; automation; goods quality; structural change; reallocations; growth; nonhomothetic preferences; hierarchical demand